The Contribution of Immune Infiltrates to Ototoxicity and Cochlear Hair Cell Loss - Wood, Megan B.; Zuo, Jian (Frontiers in Cellular Neuroscience, 2017)
Cells of the immune system have been shown to infiltrate the cochlea after acoustic trauma or ototoxic drug treatment; however, the contribution of the immune system to hair cell loss in the inner ear is incompletely understood. Most studies have concentrated on the immediate innate response to hair cell damage using CD45 as a broad marker for all immune cells. More recent studies have used RNA sequencing, GeneChip arrays, and quantitative PCR to analyze gene expression in the entire cochlea after auditory trauma, leading to a better understanding of the chemokines and cytokines that attract immune cells to the cochlea. Immune suppression by blocking cytokines or immune receptors has been proven to suppress hair cell damage. However, it is now understood that not all immune cells are detrimental to the cochlea. CX3CR1+ resident macrophages protect hair cells from damage mediated by infiltrating immune cells. Systemically, the immune response is associated with both protection and pathology, and it has been implicated in the regeneration of certain tissues after injury. This review focuses on the studies of immune cells in various models of hearing loss and highlights the steps that can be taken to elucidate the connection between the immune response and hearing loss. The interplay between the immune system and tissues that were previously thought to be immune privileged, such as the cochlea, is an emerging research field, to which additional studies of the immune component of the cochlear response to injury will make an important contribution.